Petite histoire de la géographie dans le Québec et à l’université Laval - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1962)
The development of geography in the province of Québec and its establishment as a course of study at Université Laval are described. For the province of Québec the writer defines five major periods of development of geography ; pre 1830 ; 1830-1880 ; 1880-1910 ; 1910-1945 ; and 1945 to the present. The last period represents the organisational phase of geography in the province and is by far the most important. Among other things, the reasons for the late appearance of geography are analysed and the present state of teaching and research in the province are outlined. Outside influences upon Québec geography are also discussed.The establishment of modem geography at Université Laval is outlined under three beadings :a) 1942-Sept. 1948 — the precursors. b) 1948-1954 — the establishment of geography in the program of the Faculté des lettres (teaching begins in September, 1948, the Cahiers in May, 1952, and summer courses in July, 1954). c) 1955 to the present —• the period of autonomy and expansion (organisational changes, periodicity of the Cahiers, the Mélanges Blanchard, symposia at the provincial level, and the establishment of the Centre d'études nordiques).In enterprise and achievement Laval bas played a leading role in the French-Canadian school of geography. The writer concludes by proposing a short term program for geography in Québec and at Université Laval.